1993
DOI: 10.1159/000247226
|View full text |Cite
|
Sign up to set email alerts
|

Fingertip Tophi without Gouty Arthritis

Abstract: We report 2 patients without a history of acute gouty arthritis showing tophi located only on the fingertips, an unusual location. A review of the literature found a few similar reports; these patients might represent a subgroup of gout characterized by: (1) elderly patients, from the 7th to 9th decades; (2) hyperuricemia; (3) absence of a history of acute gouty arthritis; (4) tophi in the fingertips or fingerpads; (5) chronic renal failure, and (6) all taking drugs or suffering from a disease that affects ura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Recent imaging studies revealed MSU crystal deposition and subclinical joint and extra-articular damage in people with asymptomatic hyperuricemia [ 13 18 ]. Many people with tophi also never develop acute arthritis [ 19 21 ]. These observations indicate that MSU crystals alone are not sufficient to induce acute gouty arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent imaging studies revealed MSU crystal deposition and subclinical joint and extra-articular damage in people with asymptomatic hyperuricemia [ 13 18 ]. Many people with tophi also never develop acute arthritis [ 19 21 ]. These observations indicate that MSU crystals alone are not sufficient to induce acute gouty arthritis.…”
Section: Introductionmentioning
confidence: 99%